Hybrid Fuzzy-PID for Temperature and Water Quality Control in Freshwater Lobster Farming - Arifuddin, Rahman; Setiawan, Aries Boedi; Sumarahinsih, Andrijani; Sonalitha, Elta; Kartika Sari, Resi Dwi Jayanti; Iman Mufti, Akbarsyah Nur (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2026)
General Background: Freshwater lobster aquaculture requires stable temperature and water quality conditions to support optimal growth and survival. Specific Background: Conventional and semi-automatic aquaculture control systems often experience limitations in responding to dynamic environmental changes, particularly in maintaining stable temperature, pH, and dissolved oxygen (DO) conditions in freshwater lobster cultivation. Knowledge Gap: Existing aquaculture studies predominantly focus on sensor monitoring and data transmission, while limited research has developed adaptive automatic control systems integrating fuzzy logic and PID control for simultaneous temperature and water quality stabilization in freshwater lobster farming. Aims: This study aims to design, implement, and evaluate a hybrid fuzzy-PID control system for regulating temperature and water quality in freshwater lobster (Cherax quadricarinatus) cultivation media. Results: The system utilized temperature, pH, and DO sensors, a microcontroller-based processing unit, and actuators consisting of a heater, aerator, and circulation pump. At a temperature setpoint of 28°C, the hybrid fuzzy-PID achieved a rise time of 8.7 minutes, settling time of 14.2 minutes, overshoot of 0.36%, and steady-state error of 0.03°C, outperforming conventional PID and uncontrolled systems. The hybrid approach also produced lower MAE and RMSE values of 0.393 and 0.660, respectively. Water quality evaluation showed more stable pH and DO conditions, with pH reaching 7.39 and DO reaching 6.47 mg/L. Novelty: This study integrates adaptive fuzzy inference and PID parameter adjustment within a closed-loop aquaculture control framework for simultaneous temperature and water quality management. Implications: The proposed system supports adaptive aquaculture automation and stable freshwater lobster cultivation environments for modern aquaculture applications.